The Effect of Tree Shade and Pruning Techniques on Screw Tree (Helicteres isora Linn.) Fruit Productivity in the Natural Habitat - Dani , Dani Pamungkas; Siswadi , Siswadi Siswadi (Forestry Department, University of Muhammadiyah Makassar, 2020)
Screw tree (Helicteres isora Linn.) is a shrub species with 5 to 15 main stems where the natural distribution can be found in South Timor Tengah (TTS) regency of East Nusa Tenggara (NTT) province and it is potential as a medicinal plant. The fruits are the main material harnessed for traditional medicine or jamu. Recently, little is known on fruit productivity of screw tree under shaded and open area. At the field showed that there were differences on fruit and flower production under two shade condition and the main stems. The research aimed for gaining information on the effect of pruning on screw tree fruit productivity in the natural habitat under two shade conditions on fruit productivity. Split plot design was employed with two factors which were two shade conditions (shaded under trees and open) as a main plot and the pruning techniques as a sub plot. Pruning techniques had affected significantly on the number of shoots and fruits, and there was an interaction between treatments to the number of fruits. Shade conditions had an important role on fruit production. Plants grew under open space had better fruit characteristics on fruit length (46,94 cm), fruit diameter (6,41 mm), post-harvest fruit weight (0,94 g), oven-dried fruit weight (0,89 g) and lower water content (5,57 %), compared to under shaded space 44,16 mm; 5,73 mm; 0,87 g; 0,81 g and 6,95 %, respectively for fruit length, fruit diameter, post-harvest fruit weight, oven-dried fruit weight and fruit water content.